Robust Watermarking for Color Images using SVD with Column/ Row Wavelet transforms in Low and Mid-frequency spectrum of host - Kekre, H.B.; Sarode, Tanuja; Natu, Shachi (European Journal of Applied Sciences, 2015)
<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 12pt; mso-fareast-font-family: SimSun; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">This paper proposes a joint SVD and wavelet transform based watermarking technique. Host and watermark images are column/row transformed using wavelet transforms like DCT wavelet, Walsh wavelet, Haar wavelet and DKT wavelet. These wavelet transforms are generated from orthogonal transforms DCT, Walsh, Haar and DKT. Generally middle frequency region of transformed host is used to hide the watermark. However, in proposed technique, stability of SVD is exploited to hide the watermark in low frequency region of host. Singular values of low as well as middle frequency region of transformed host are altered with suitable scaling factors to hide the watermark. Performance of the technique is tested under compression, cropping, noise addition and resizing attack. Use of low frequency region in proposed method shows strong robustness for all attacks except cropping and is immediately followed by use of mid-frequency region. To sustain against cropping attack, mid-frequency region is found to be more suitable.